Change management and its contribution to the success of IT project implementation - Munassar, Fatima; Ghanim, Alyaa; Ahmad Dahlan, Abdul Rahman (Journal of Information and Communication Technology (JICT), 2013)
Witnessing our contemporary time, Technology and its rapid advancement could make a tremendous impact on every aspect of our life. Technology has been used in various daily life operations regardless of their fields. Most business sectors have moved toward ICT and consider it as one of potential competitive advantages. Thus, more IT projects are conducted. It has been shown that the numbers of IT projects failure are currently high and this due to various factors but the main factor stated was poor project management. Additionally, time gets change from day-to-day rapidly and creating a dynamic organization becomes very challenging. Projects are long-term process where project management is short-term process. Therefore, proper management is required to ensure the effectiveness of the projects implementation plus felicitous change management is much demanded since it focuses on the enhancement of the projects after being implemented to cope with the current massive change aspect to ensure the productivity and sustainability of any organizations.